Microstructural Features Intimated in Automotive Grade IF Steel Subjected to Conventional and Severe Shot Peening - Sahoo, Bibekananda; Udaya Bhat, K. (Metallography, microstructure, and analysis, 2024)
A significant amount of interstitial-free or IF steel is used to manufacture automotive body parts due to its high ductility, high formability, and low yield strength. But, the major drawback of this steel is the lower surface hardness. The current investigation intended to enhance the surface hardness by employing shot peening at different coverages. The work also studied the microstructural features intimated after the treatment and its effect on the surface hardness. The optical and transmission electron microscopy (TEM) results showed a prominent grain refinement and dislocation hardening, which improved the micro-hardness to 2.5 times. Tri-junctions, sub-grains, twins, nanocrystalline regions, and several dislocation-induced microstructural features, like dislocation bands, dislocation forests, dislocation walls, dislocation cell structure, etc., were detected in the samples after peening. These features bear a beneficial impact on the surface hardness of the substrate. A spatial filter (Sobel filter) was used to refine the image and detect the presence of NbC precipitates near the grain boundary. Using Gatan DigitalMicrograph software, the thermal imaging technique effectively identified thinner grain boundaries near the segregation zone.